UK Research Priorities for Electronic Cigarettes: A James Lind Alliance Priority Setting Partnership - Hunter, Abby (Int J Environ Res Public Health, 2020)
This study aimed to bring together people who smoke or vape, people who do not smoke and healthcare professionals to identify and agree priorities for electronic cigarette research in the UK. We carried out a priority setting partnership, guided by the methodology developed by the James Lind Alliance involving five key stages: initiation, consultation, collation, prioritisation and dissemination. A total of 765 people submitted 1887 questions that they wanted answered by research. Questions were organised into themes, merged and rewritten as summary questions, with 52 unique questions going forward to the prioritisation survey. Participants then ranked their top 10 questions. Following this ranking exercise, the top 26 were identified by selecting the most frequently prioritised questions adjusting for representative stakeholder group. These were put forward for discussion in the final prioritisation workshop, whereby the top 10 electronic cigarette research questions were agreed. The list of priorities identified will be of interest to researchers and funders of electronic cigarette research and will hopefully direct future research and funding calls. These priorities provide insight into the questions that matter to people who are using or concerned about e-cigarettes, including frontline professionals.